The restorative nature of ongoing connections with the deceased : exploring presence within absence - Burke, Laurie A.; Rynearson, Edward K. (New York, NY : Routledge, 2022)
"The Restorative Nature of Ongoing Connections with the Deceased is a guide to stimulating thought and discussion about ongoing attachments between bereaved individuals and their deceased loved ones. Chapters promote broad, inclusive training and dialogue for working with clients who establish and/or maintain a restorative connection with their deceased loved one as well as those who find aspects of such connections to be psychologically or spiritually problematic or troublesome. Bereavement professionals will come away from this book with a better understanding and a deeper skillset for helping clients to develop continuing bonds"--
Keywords: Bereavement -- Psychological aspects; Bereavement -- Religious aspects; Loss (Psychology); Death -- Psychological aspects; PSYCHOLOGY / Psychotherapy / General; PSYCHOLOGY / Mental Health